Evaluating the feasibility of performing pharmacogenetic guided‐medication therapy management in a retirement community: A prospective, single arm study. Issue 3 (12th December 2021) - Chaitesipaseut, Lena; Wilson Norton, Jennifer; Trivelli, Kristen; Argon, Sophie; Petrie, Ichiko; Ragueneau‐Majlessi, Isabelle; Mikes, Tamatha; Nguyen, Hao; Devine, Beth
Abstract: Introduction: Pharmacogenomic‐guided medication therapy management (PGx‐MTM) can optimize medication therapy for older adults. Pharmacist‐led PGx‐MTM in retirement communities has been infrequently described. Objectives: We conducted a prospective, single‐arm feasibility study that incorporated PGx‐MTM services into an academic clinical practice at a retirement community. We posited that provision of PGx‐MTM services would be feasible and would enable us to identify one or more drug therapy‐related problems for each participant. Methods: We screened residents using a predefined list of gene‐drug pairs for which the level of evidence for clinical impact is highest and consented those who were taking one of these medications ( qualifying medication ). The clinical pharmacist conducted PGx testing using a DNA buccal swab. Tests were analyzed by a commercial laboratory, and a corresponding Personalized Medicine Report generated. The Report included an assessment of gene‐drug pairs not only for qualifying medications, but for all pairs on our predefined list, in the event participants were prescribed these medications in the future ( future medications ). Results were risk‐categorized as "consider alternatives, " "use with caution, " or "standard precautions" (no change in therapy).The clinical pharmacist reviewed participant‐specific results for all gene‐drug pairs tested, then forwarded results to participants' providers along with recommendations for modifications in drug therapy. We calculated descriptive statistics to characterize participant‐specific demographic and clinical characteristics, medication use, PGx test results, and corresponding recommendations. Results: Eighteen participants enrolled. We evaluated 23 results of qualifying medications, associated with six genes, 30% (7/23) of which were categorized as "use with caution" (warfarin) or "consider alternatives" (simvastatin, clopidogrel, and paroxetine). One required a change in therapy (simvastatin). When considering future medications (n = 245), the proportion was the same. Conclusion: Our work demonstrates the feasibility of and suggests the potential for providing PGx‐MTM in retirement communities using preemptive genotyping, offering a new level of care to an often‐overlooked population, and advancing pharmacy practice.